Broodstock Nutrition of Australian Red Claw Crayfish Cherax Quadricarinatus (Von Martens) - Asgari, Ladan (2004)
A series of experiments were conducted to develop least cost feed formulations for red claw crayfish Cherax quadricarinatus broodstock based on the gonad, egg protein and essential amino acids content . All diets were developed using least cost feedstuffs and a linear interactive and discrete optimiser software (LINDO). Prior to evaluation of different formulated diets, the protein and amino acid contents of red claw crayfish broodstock tissues, eggs and newly hatched juvenile under a culture condition were analysed. Increases in ovarian and embryonic proteins content from 10.48 to 65.29 % were observed with the maturation stages of red claw crayfish C. quadricarinatus. These results emphasized the critical role of protein as a main structural component in - maturation. However, amino acid compositions of gonad and embryonic tissue of C. quadricarinatus were generally remained constent with the possible exception of histidine. A comparative study on performance of five dietary protein levels (30-50%) on red claw crayfish was carried out. Based on spawning rate, fecundity, s hatchability and egg size, a range of 40-45% crude protein and 16.72 kJ g-' (400 kcal 100 g-l) energy were the bestloptimal for red claw crayfish broodstock. Eessential amino acids index (EAAI) of all test diets (developed based on available least cost ingredients for red claw crayfish broodstock) were within the best range (0.960-0.996) recommended for crustaceans. Therefore, all test diets were best in terms of protein and essential amino acids sources. In term of biochemical composition, an increase in dietary protein l eve1 was a Iso i ncreased the protein content i n eggs a nd muscle. A positive relationship between dietary protein level and protein contents of eggs and muscle of red claw broodstock was found. A following study later showed that a diet providing 40% protein and 16.72 k~g-('4 00 kcal 100 g-') energy or 45% protein and 14.65 -16.72 kJ g" (350- 400 Kcal 100 gel) energy could support a higher eggs production and hatchability in red claw broodstock. In this study, at a constant dietary protein level, broodstock performance increased with an increase in dietary energy level. Whereas, feeding red claw crayfish brood stock with lower energy diets resulted in a noticeable reduction in spawning rate and a delay of 2-3 weeks in the time of onset of spawning. The extremely low performance of red claw crayfish broodstock fed with low dietary energy content suggested the important role of energy in its reproduction and metabolism.